An active control strategy to suppress nonlinear vibrations of large space membranes. (February 2019) - Shi, Hang; Wang, Chao; Liu, Lilan; Gao, Zenggui; Xie, Yangmin
Abstract: Large space membranes have been widely used in many space projects to develop extremely large and lightweight SAR antennas, solar arrays and solar sails, and the nonlinear structural vibrations induced by on-orbit disturbances should be suppressed to satisfy the mission requirements. In this paper, the nonlinear dynamic behaviors of a typical large space membrane, which can not be accurately described by natural frequencies and mode shapes, are investigated by the trustworthy iterative membrane property modeling approach. Based on the discussions of the controller design challenges from such nonlinearity, this paper proposes a distributed control strategy to actively suppress the nonlinear membrane vibration, and comparatively evaluates three different actuating and sensing placements to obtain superior vibration suppression performance. Very promising results numerically demonstrate that the proposed control strategy is theoretically feasible and has great potential to be used in the design of active vibration suppression systems for large space membrane applications. Highlights: Nonlinear vibration behaviors are investigated on a typical large space membrane. A distributed control strategy is proposed to suppress nonlinear membrane vibrations. Superior performance is obtained by examining actuating/sensing placement strategies.